Designing Intelligent Nanomaterials to Achieve Highly Sensitive Diagnoses and Multimodality Therapy of Bladder Cancer (Small Methods 2/2023). Issue 2 (17th February 2023) - Li, Guanlin; Wu, Sicheng; Chen, Wenzhe; Duan, Xiaolu; Sun, Xinyuan; Li, Shujue; Mai, Zanlin; Wu, Wenzheng; Zeng, Guohua; Liu, Hongxing; Chen, Tianfeng
Abstract : Bladder Cancer Theranostics In article number 2201313, Zeng, Liu, Chen, and co‐workers summarize the application of nanotechnology in bladder cancer diagnosis and their potential applications in bladder cancer therapy regarding increasing drug retention and adhesion, enhancing drug penetration, overcoming drug resistance, and improving drug targeting. This review presents an overview of the application of nanomaterials‐based bladder cancer theranostics.